2023
DOI: 10.3390/jcm12144576
|View full text |Cite
|
Sign up to set email alerts
|

Renal Manifestations of Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Syndrome: A Systematic Review of 71 Cases

Marilia Dagnon da Silva,
Sidney Marcel Domingues,
Stevan Oluic
et al.

Abstract: Unlike other adverse drug reactions, visceral organ involvement is a prominent feature of drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome and correlates with mortality. The aim of this study was to systematically review cases published in PubMed-indexed, peer-reviewed journals in which patients had renal injury during the episode of DRESS syndrome (DS). We found 71 cases, of which 67 were adults and 56% were males. Female sex was associated with higher mortality. Chronic kidney disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 151 publications
1
8
0
Order By: Relevance
“…The diagnostic criteria of DRESS syndrome include the suspicion of a drug-related reaction as well as the occurrence of acute rash, fever (>38°C), lymphadenopathy, hematologic abnormalities, and systemic involvement ( Martins et al, 2021 ). The systemic involvement of internal organs may manifest as hepatitis, nephrotoxicity, pneumonitis, cerebral edema, eosinophilia, pericardial effusion, leukocytosis, myocarditis, or thyroiditis ( Taweesedt et al, 2019 ; Radovanovic et al, 2022 ; Dagnon da Silva et al, 2023 ). In our case, the patient had pharyngitis, lymphadenopathy, AKI, hepatitis, and splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic criteria of DRESS syndrome include the suspicion of a drug-related reaction as well as the occurrence of acute rash, fever (>38°C), lymphadenopathy, hematologic abnormalities, and systemic involvement ( Martins et al, 2021 ). The systemic involvement of internal organs may manifest as hepatitis, nephrotoxicity, pneumonitis, cerebral edema, eosinophilia, pericardial effusion, leukocytosis, myocarditis, or thyroiditis ( Taweesedt et al, 2019 ; Radovanovic et al, 2022 ; Dagnon da Silva et al, 2023 ). In our case, the patient had pharyngitis, lymphadenopathy, AKI, hepatitis, and splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review summarized 71 cases with renal manifestations of DRESS syndrome showed that AKI was the most common manifestation in 96% of the patients. 27% had AKI with proteinuria and anuria was the rarest manifestation ( Dagnon da Silva et al, 2023 ). The mortality rate associated with DRESS syndrome is 10%–20% usually due to myocarditis or hepatotoxicity ( Heymann, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare life‐threatening adverse drug reaction characterized by multiple organ involvement 1 including the liver, 2,3 lungs, 4 heart, 5 gastrointestinal system, 6 and kidneys 7–9 . DRESS presents with fever and skin rash, lymphadenopathy, internal organ involvement, and hematological alteration 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This can be determined by elevated serum creatinine (SCr) levels, decreased glomerular filtration rate (GFR), or hematuria, proteinuria, and eosinophiluria. [ 6 ] The differential diagnosis of DRESS syndrome includes other cutaneous adverse drug reactions, such as Stevens-Johnson syndrome/toxic epidermal, necrolysis autoimmune diseases, such as acute cutaneous lupus erythematosus, and lymphomas, hypereosinophilic syndromes, and viral infections. In the case of renal involvement, it is important to differentiate DRESS from drug-induced acute interstitial nephritis, which often manifests with the triad of rash, fever, and eosinophilia.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of renal involvement, it is important to differentiate DRESS from drug-induced acute interstitial nephritis, which often manifests with the triad of rash, fever, and eosinophilia. DRESS is usually accompanied by involvement of other internal organs and features, such as lymphadenopathy and facial swelling, that are absent in interstitial nephritis [ 6 ]. The Registry of Severe Cutaneous Adverse Reactions (RegiSCAR) scoring system is used to confirm or exclude the diagnosis of DRESS [ 2 ].…”
Section: Introductionmentioning
confidence: 99%